Pathways to Post-Secondary Education: A Multi-Method Investigation of the Impacts of Support Systems and School Belonging on Students’ Post-Secondary Intentions - Pulchny, Alexandra (My University, 2025)
This dissertation explores the factors influencing students’ transitions into post-secondary education (PSE) in Canada, focusing on the roles of family, school, and community support systems. The first chapter provides a systematic review of the literature on student transitions, identifying key influences such as family dynamics, geography, and race. The second chapter examines how students' sense of belonging – shaped by parental support, school environment, and teacher relationships – affects their PSE intentions, with a focus on the mediation relationship of race and gender and the moderating relationship of streaming and race. The third chapter presents a case study of an after-school STEM program engaging at-risk and underrepresented youth in Hamilton, Ontario, highlighting the program’s role in fostering academic and personal growth, positive PSE attitudes, and sense of belonging. Through this exploration, the dissertation emphasizes the importance of supportive structures both in and outside of school in facilitating successful transitions to PSE. The findings contribute to understanding how educational systems can better support at-risk students in achieving their post-secondary goals.
Keywords: Post-Secondary Education Transitions; Sense of Belonging; Support Systems; Canada